TRADISI PADUNGKU MASYARAKAT DESA MALEKU KECAMATAN MANGKUTANA KABUPATEN LUWU TIMUR SEBAGAI SUMBER BAHAN AJAR MATERI GEOGRAFI DI SMA NEGERI 4 LUWU TIMUR - Budianto, Adi (LaGeografia, 2018)
This study aims 1). to know the process, 2). values, 3). the meaning of my traditional tradition in Maleku Village, Mangkutana Subdistrict, East Luwu Regency. 4). to know the position of traditional values padungku as a source of teaching materials learning materials Geography at SMAN 4 East Luwu. The type of this research is qualitative research using ethnography approach. Data collection techniques, 1). Observation, 2). Interview / interview, 3). Documentation. Data analysis techniques, namely 1). Reduction of data, 2). Presentation (display) data, 3). Conclusion / verification. The results showed that. Tradition Padungku in Maleku Village, District Mangkutana emerged when people began to open forests to farm, then there also appears to make a thanksgiving. Since the existence of Padungku religion at this time to be different meaning and different nuances. My fox was adopted by the church to be a thanksgiving feast not only for farmers but for all other kinds of work. Since the year 2000an practically no longer held the village hall, otherwise the harvest feast done in the church. 1). Stages in carrying out the tradition padungku that is, a). the timing of the implementation of my traditional tradition, b). Place of execution of my padungku tradition, c). equipment in the tradition of my paddle. 2). The values contained in the tradition are, a). religious, b). tolerance, c). hard work, d). responsibility, e). care about the environment, f). the value of art preservation, g). solidarity, and h). democratic values. 3). The tradition of my paddle means an expression of gratitude to the Almighty God for the harvest. 4). Associated with these values can be used as a source of teaching materials Geography learning materials in SMA that is, a). hard work, b). tolerance, c). responsibility, d). care about the environment, in order to instill good character in each student. Implementing the tradition of padungku, there are values and meaning is good to be cultivated to students to form the character of students.